A mixed methods study of the work patterns of full‐time nurse practitioners in nursing homes. Issue 9 (19th December 2014) - Martin‐Misener, Ruth; Donald, Faith; Wickson‐Griffiths, Abigail; Akhtar‐Danesh, Noori; Ploeg, Jenny; Brazil, Kevin; Kaasalainen, Sharon; McAiney, Carrie; Carter, Nancy; Schindel Martin, Lori; Sangster‐Gormley, Esther; Taniguchi, Alan
Abstract : Aims and objectives: The aim of this study was to explore the integration of the nurse practitioner role in Canadian nursing homes to enable its full potential to be realised for resident and family care. The objective was to determine nurse practitioners' patterns of work activities. Background: Nurse practitioners were introduced in Canadian nursing homes a decade ago on a pilot basis. In recent years, government and nursing home sector interest in the role has grown along with the need for data to inform planning efforts. Design: The study used a sequential mixed methods design using a national survey followed by case studies. Methods: A national survey of nurse practitioners included demographic items and the EverCare Nurse Practitioner Role and Activity Scale. Following the survey, case studies were conducted in four nursing homes. Data were collected using individual and focus group interviews, document reviews and field notes. Results: Twenty‐three of a target population of 26 nurse practitioners responded to the survey, two‐thirds of whom provided services in nursing homes with one site and the remainder in nursing homes with as many as four sites. On average, nurse practitioners performed activities in communicator, clinician, care manager/coordinator and coach/educator subscales at least three to four times per week and activities in the collaborator subscale once a week. Of the 43 activities, nurse practitioners performed daily, most were in the clinician and communicator subscales. Case study interviews involved 150 participants. Findings complemented those of the survey and identified additional leadership activities. Conclusion: Nurse practitioners undertake a range of primary health care and advanced practice activities which they adapt to meet the unique needs of nursing homes. Relevance to clinical practice: Knowledge of work patterns enables nursing homes to implement the full range of nurse practitioner roles and activities to enhance resident and family care.